The Mediation Effectiveness of Green Supply Chain Management Practices Toward Sustainable Development in Algerian Construction Industry - Harouache, Ahmed; Chen, Goh Kai; Sarpin, Norliana Binti; Hamawandy, Nawzad Majeed; Abubakr, Zaito Awla; lbrahim, Shorsh; Othman, Bestoon; Othman, Baban Jabbar (The journal of contemporary issues in business and government, 2021)
Sustainable construction involves the creation of buildings using best-practice cleansing and resource-saving technologies from the extraction of raw materials to the removal and disposal of their components. Construction activities always involves some adverse environmental impacts, although sustainable construction should reduce it to a certain degree. Management scholars researched organizational environmental practices in 1990s and advocated more holistic and responsible practices in the supply chain. The aim of the study is to improve the use of green supply chain in construction industry sector in Algeria. Firms that are targeted in this study are Suppliers, Managers and Contractors in Algeria. Supply Chain Management (SCM) is still in its infancy in the construction industry, but some philosophical awareness is evident. Suppliers, contractors and subcontractors are not integrated, they lack teamwork and they are not team-oriented. GSCM can play an important role in architecture. The adoption of GSCM provides general guidelines for analyzing, redesigning, and coordinating the entire supply chain of the building and continuous improvement, solving basic problems and controlling short-sighted supply chains. This paper has proposed a conceptual framework for this study by exiting all these saturated areas into the construction industry sector with attention to the intensity of implementation of green supply chain management in the construction industry sector in Algeria.